Practical applications in the development of E-commerce : www.HollandVillage.com.sg. - Tan, Ian Kok Chun (2008)
This report demonstrates the practical application in the development of www.hollandvillage.com.sg. This report also shows a brief documentation of our development of the e-business. It can serve as a guide to groups who want to set up a commercial website in the future.